Feeding dysfunctions and failure to thrive in neonates with congenital heart diseases - Giovanna Mangili; Elena Garzoli; Youcef Sadou (PAGEPress Publications, 2018)
Congenital heart disease (CHD) is the most common neonatal congenital malformation. The variety and severity of clinical presentation depend on the cardiac structures involved and their functional impact. The management of newborns with CHD requires a multidisciplinary approach, in which the nutritional aspect plays an important role. An adequate caloric intake during either preand post-surgical period, in fact, improves the outcome of these patients. In addition, the failure to thrive of these children in childhood has been related to long-term cognitive delay (attention deficit disorders, aggressive behaviour and poor social and emotional development). To date, there is a lack of standardized feeding protocols and caloric goals about how to feed neonates with CHD, and current practice varies widely between centres. The latest American Society for Parenteral and Enteral Nutrition guidelines reiterate the importance of proteins, and recommend early start of enteral nutrition, also in the most severe heart diseases, such as univentricular forms. Necrotizing enterocolitis (NEC), the most frequent and feared complication of early feeding of these newborns, often represents an obstacle in spreading this practice. Furthermore, as demonstrated in premature infants, breastfeeding seems to reduce the incidence of NEC. That is why breastfeeding must be encouraged, even if it can be difficult for these mothers due to delivery complications, associated with infant disease. In addition, eating difficulties may persist even after discharge, because these patients require nutritional support through nasogastric tubes or percutaneous endoscopic gastrostomies.